Association between Life’s Essential 8 and psoriasis in US adults: a cross-sectional study - Zhang, Junjie; Ren, Ci; Qin, Zihan; Zhu, Ling; Jin, Zhoufeng; Yan, Yuanyuan; Pan, Xinghe; Luan, Lan (Frontiers in Medicine, 2024)
Background: Psoriasis is closely associated with cardiovascular disease (CVD).However, the current evidence on the correlation between Life's Essential 8 and Psoriasis is insufficient. Our aim was to investigate the relationship between Life's Essential 8 (LE8), a measure of cardiovascular health (CVH), and psoriasis. Objective: This study aimed to clarify the impact of Life's Essential 8 on Psoriasis and explore its implications. Methods: This population-based cross-sectional study included 9,876 US adults aged 20 to 59 years from the National Health and Nutrition Examination Survey (NHANES) 2003-2006 and 2009-2014 cycles. The LE8 score comprises 8 metrics and was categorized into low, moderate, and high CVH. Logistic regression and restricted cubic splines (RCS) were used to assess the association between LE8 score and psoriasis.Results: Among the 9,876 participants, those with moderate and high CVH had higher risks of psoriasis compared to low CVH. Additionally, every 10-point increase in the LE8 score was associated with a 10% reduced risk of psoriasis. Interaction was observed between gender, age, education level, race/ethnicity, marital status, and PIR. Conclusion: LE8 and its subscale scores were strongly negatively related to the risk of psoriasis. Encouraging optimal CVH levels may be advantageous in reducing the incidence of psoriasis.